2022
DOI: 10.1186/s13071-022-05305-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial statistical and environmental correlation analyses on vector density, vector infection index and Japanese encephalitis cases at the village and pigsty levels in Liyi County, Shanxi Province, China

Abstract: Background In the eco-epidemiological context of Japanese encephalitis (JE), geo-environmental features influence the spatial spread of the vector (Culex tritaeniorhynchus, Giles 1901) density, vector infection, and JE cases. Methods In Liyi County, Shanxi Province, China, the spatial autocorrelation of mosquito vector density, vector infection indices, and JE cases were investigated at the pigsty and village scales. The map and Enhanced Thematic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Temperature affects mosquito development and viral replication in an amplifying host and vector, and appropriate relative humidity allows mosquitoes to survive longer and spread further, increasing the risk of pathogen transmission ( Song et al., 2020 ; Tu et al., 2021 ). A study in Liyi County, Yuncheng City, found that cotton field water by periodic flooding generates abundant favorable breeding sites for JE vector mosquitoes, and cotton field irrigation management was beneficial for JE control in this region ( Liu et al., 2022 ). Furthermore, there was a tight association between pig number, vector infection rate, and the number of human JE cases ( Borah et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature affects mosquito development and viral replication in an amplifying host and vector, and appropriate relative humidity allows mosquitoes to survive longer and spread further, increasing the risk of pathogen transmission ( Song et al., 2020 ; Tu et al., 2021 ). A study in Liyi County, Yuncheng City, found that cotton field water by periodic flooding generates abundant favorable breeding sites for JE vector mosquitoes, and cotton field irrigation management was beneficial for JE control in this region ( Liu et al., 2022 ). Furthermore, there was a tight association between pig number, vector infection rate, and the number of human JE cases ( Borah et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Liyi County, Yuncheng City, found that cotton field water by periodic flooding generates abundant favorable breeding sites for JE vector mosquitoes, and cotton field irrigation management was beneficial for JE control in this region (Liu et al, 2022). Furthermore, there was a tight association between pig number, vector infection rate, and the number of human JE cases (Borah et al, 2013).…”
Section: Discussionmentioning
confidence: 99%